Trelleborg in Scania: Late Iron Age Settlement, Late Viking Age Ring-fort and High Medieval Town - Jacobsson, Bengt (Hikuin, 1998)
Trelleborg in Scania is a medieval town, first mentioned in 1257 in a letter between the Danish king Kristoffer and Archbishop Jacob Erlandsson in Lund. In 1957, the former head of the the museum in Trelleborg, Harald Lindal, wrote a book about the history of the town. This book was mostly based on written sources, since the archaeological material at that time was very limited. Since then a lot of excavations have taken place in Trelleborg, especially in the last ten years. This has provided us with new information, which gives us a completely new view of the medieval town and also shows us that the history of this area goes back far beyond the medieval period.